Territorialities in struggle surrounding a wind farm in Argentina - Kropff Causa, Laura (2022)
This essay addresses territorial tensions that emerged within negotiations related to a wind farm project aimed to be located in a rural setting in Río Negro province (Argentina). The project is promoted by a Chinese company and was accepted due to an Environmental Impact Assessment that missed to mention that there was a Mapuche community where the wind farm was intended to be located. Therefore, the community requested the development of a consultation process. In this process, different territorial logics were put into play, however within asymmetrical relations. The essay approaches these logics based on empirical evidence that was gathered through ethnographic fieldwork and archive research. The argument focuses on the territorial assumptions expressed in the Environmental Impact Assessment in comparison with those sustained by the community emphasizing on the ontological dimension of the problem. renewable energies – indigenous rights – mapuche – Patagonia – territoriality